2010
DOI: 10.1002/tal.647
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of a very slender building under winds: response reduction using MR dampers with lever mechanism

Abstract: This paper presents wind‐induced response reduction in a very slender building using magneto‐rheological (MR) dampers with lever mechanism. The building presents a case study of an engineered design that is instructive. The paper shows that shear response and flexural response of tall buildings present two very different cases for vibration suppression. MR dampers are implemented optimally in the building to reduce its response in the lateral directions for both structural safety and occupant comfort concerns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 7 publications
1
40
0
Order By: Relevance
“…The first six mode shapes of the full-scale tower were used in the analysis. It is worth noting that the first six modes were sufficient for accurate estimation of the response (Aly et al, 2011c). The first and fourth are flexural modes in x-dir, the second and fifth flexural modes in y-dir, and the third and sixth torsional modes.…”
Section: Evaluation Of the Dynamic Responsementioning
confidence: 99%
“…The first six mode shapes of the full-scale tower were used in the analysis. It is worth noting that the first six modes were sufficient for accurate estimation of the response (Aly et al, 2011c). The first and fourth are flexural modes in x-dir, the second and fifth flexural modes in y-dir, and the third and sixth torsional modes.…”
Section: Evaluation Of the Dynamic Responsementioning
confidence: 99%
“…passive, active and semi-active, is not only for structures subjected to earthquake excitations. There are many studies that have shown that these strategies are effective in the response reduction of buildings under strong wind loads (Huang and Chou, 1995;Wu and Pan, 2002;Aly et al, 2011;Aly, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Special attention has been paid to post‐yield stiffness as earlier studies, such as FEMA 307, Ye et al , and Pettinga et al , have shown that behaviors with positive post‐yield stiffness tend to have smaller residual deformations and better distribution of plasticity along height of the structure. Different researchers have used TOB in combination with energy dissipating devices . Non‐deteriorating TOB system is also not a new idea and has been examined before a novel connection called ribbed bracing system has been proposed by Golafshani et al for steel braces in which using a semi‐active connection, buckling‐free braces have been achieved.…”
Section: Introductionmentioning
confidence: 99%